Neuropsychiatric involvement in juvenile-onset systemic lupus erythematosus (jSLE) - Valentina Natoli; Amandine Charras; Gabriele Hahn; Christian M. Hedrich (SpringerOpen, 2023)
Abstract Systemic lupus erythematosus (SLE) is a rare autoimmune/inflammatory disease with significant morbidity and mortality. Approximately 15-20% of SLE patients develop the disease during childhood or adolescence (juvenile-onset SLE/jSLE). Patients with jSLE exhibit more variable and severe disease when compared to patients with disease-onset during adulthood. Neuropsychiatric (NP) involvement is a clinically heterogenous and potentially severe complication. Published reports on the incidence and prevalence of NP-jSLE are scarce, and the exact pathophysiology is poorly understood. This manuscript provides a review of the existing literature, suggesting NP involvement in 13.5-51% of jSLE patients. Among patients with NP-jSLE affecting the CNS, we propose two main subgroups: (i) a chronic progressive, predominantly type 1 interferon-driven form that poorly responds to currently used treatments, and (ii) an acutely aggressive form that usually presents early during the disease that may be primarily mediated by auto-reactive effector lymphocytes. While this hypothesis requires to be tested in large collaborative international cohort studies, it may offer future patient stratification and individualised care.